Serum immunoglobulin free light chain levels are higher in girls than boys during eosinophilic oesophagitis. (28th April 2014) - Knipping, Karen; Colson, Diana; Soulaines, Pascale; Redegeld, Frank; Garssen, Johan; Dupont, Christophe
Abstract Aim Eosinophilic oesophagitis (EO) is an emerging worldwide disease, closely associated with male gender and allergic disorders. This study investigated the distribution of allergy markers in a cohort of children with EO. Methods We analysed allergy markers in 91 children (62 males and 29 females) with EO and a control group of 45 age‐matched children who had non‐EO gastrointestinal allergic symptoms. The markers analysed were serum cow's milk‐specific and hen's egg‐specific IgE, thymic stromal lymphopoietin (TSLP), thymus‐regulated and activation‐regulated chemokine (TARC/CCL17) and immunoglobulin free light chain (Ig‐fLC). Results In the EO group, cow's milk‐specific IgE levels were detectable in 41.9% of males and 62.1% of females and hen's egg‐specific levels in 25% of males and 26.9% of females. There was no gender difference in increased TSLP or TARC levels. Kappa Ig‐fLC were increased in 5.6% of males and 20.8% of females (p = 0.058) and lambda Ig‐fLC in 1.9% of males and 33.3% of females (p = 0.000). No gender differences were found in the control group. Conclusion Our findings suggest that serum TSLP might be a potential marker of EO and TARC of non‐EO gastrointestinal food allergies. In EO, serum Ig‐fLC appeared higher in females, adding another gender difference to the biology of EO.